Navigating the Glass Ceiling: Women’s Career Challenges in Nepal’s Banking Sector - Shrestha, Sajeeb Kumar; Parajuli, Suman Kamal; Dhungel, Diksha (NPRC Journal of Multidisciplinary Research, 2024)
Background: Glass ceiling factors, such as organizational, social, and psychological barriers, continue to hinder women’s career advancement, particularly in managerial roles. Despite increasing efforts to promote gender equality in the workplace, these factors still limit opportunities for women’s development, especially in traditionally male-dominated industries like banking in Nepal. This study investigates how these factors influence women’s perceptions of career development and whether they significantly impact their progress. Methods: The research employed a quantitative approach using a structured questionnaire distributed to 51 respondents in the banking sector. The survey measured perceptions of organizational, social, and psychological factors impacting women’s career development. Multiple regression analysis was used to assess the impact of these factors on personal factors related to career growth. Descriptive statistics and correlation analyses were also performed. Results: The findings indicate that social factors significantly influence personal factors (B = 0.257, p = 0.035), suggesting that social barriers are key determinants of women’s career development. Organizational and psychological factors, while positively related to personal factors, did not show statistically significant effects (OFFF: B = 0.159, p = 0.164; PSFFF: B = 0.144, p = 0.275). The model explained 29.5% of the variance in personal factors, highlighting that additional unexamined factors may influence women’s career perceptions. Conclusion: Social factors have a significant impact on women’s perceptions of career barriers, underscoring the need to address societal norms and biases that prevent women from advancing. Organizational and psychological factors, although relevant, were not statistically significant in this context. The study contributes to understanding the dynamics of the glass ceiling, particularly within Nepal’s banking sector, and provides insights for policy and organizational change. Novelty: This study offers a unique perspective on the glass ceiling in the Nepalese banking sector, providing empirical evidence of how social factors predominantly influence women’s career progression. The findings suggest targeted interventions to address these barriers and promote more equitable career advancement opportunities for women in managerial roles.